An Antihyperkinetic Action by the Serotonin 1A-Receptor Agonist Osemozotan Co-administered With Psychostimulants or the Non-stimulant Atomoxetine in Mice - Rie Tsuchida; Masahiro Kubo; Mariko Kuroda; Yasuhiro Shibasaki; Norihito Shintani; Michikazu Abe; Katalin Köves; Hitoshi Hashimoto; Akemichi Baba (Elsevier, 2009)
It has been demonstrated that treatment of hyperactive mice with psychostimulants produced a calming effect depending on serotonergic neurotransmission. Our previous study also showed that hyperactivity in mice lacking pituitary adenylate cyclase-activating polypeptide (PACAP) was ameliorated by amphetamine in a serotonin (5-HT)1A-dependent manner and that amphetamine calmed wild-type mice given the 5-HT1A agonist 8-OH-DPAT. Here, we examined if 5-HT1A-mediated pathways can be a determinant of the action of other psychostimulants as well as the non-stimulant atomoxetine by examining locomotor activity in mice co-administered with the 5-HT1A agonist osemozotan. Co-administration of osemozotan with either methamphetamine or amphetamine was not only antihyperkinetic, but also decreased locomotion to below basal levels. In contrast, osemozotan just nullified methylphenidate-induced hyperactivity. The non-stimulant atomoxetine did not induce hyperactivity, but co-administration of atomoxetine with osemozotan produced a calming effect. The adjunctive effect of osemozotan added to the psychostimulants was blocked by the 5-HT1A antagonist WAY-100635 at a low dose (0.1 mg/kg), suggesting the involvement of a presynaptic 5-HT1A-mediated mechanism. However, WAY-100635 (up to 1 mg/kg) did not block the effect of atomoxetine plus osemozotan. The present results may provide insights into the therapeutic mechanisms of the psychostimulants and atomoxetine for hyperkinetic disorders. Keywords:: atomoxetine, attention-deficit/hyperactivity disorder (ADHD) medication, locomotor activity, psychostimulant, serotonin 5-HT1A receptor